Analisis Perbandingan Perhitungan Pajak Penghasilan Badan Metode Final dan Tidak Final pada PT Rahmat Indonikel Abadi - Muslimah, Hamidah; Annas, Nurul Afiqah (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
This study aims to analyze the calculation of corporate income tax at the mining contractor service company PT Rahmat Indonikel Abadi for the 2021 period. The research employs a descriptive quantitative method using secondary data. The type of data utilized is quantitative data, collected through documentation study, interviews, and observation. The subject of this research is the calculation of corporate income tax. The findings indicate that the more cost-effective method for PT Rahmat Indonikel Abadi in calculating its corporate income tax liability is by applying the Final Income Tax Calculation, in accordance with Government Regulation No. 23 in conjunction with Government Regulation No. 55, at a rate of 0.5% of the company’s gross turnover. The tax payable refers to the tax that must be settled within both the tax period and the fiscal year. This study concludes that the application of the final income tax calculation provides greater efficiency for the company by reducing its tax payment burden.